Upward gas–liquid two-phase flow after a U-bend in a large-diameter serpentine pipe - Aliyu, Aliyu M.; Almabrok, Almabrok Abushanaf; Baba, Yahaya D.; Lao, Liyun; Yeung, Hoi; Kim, Kyung C. (Elsevier, 2017)
We present an experimental study on the flow behaviour of gas and liquid in the upward section of a vertical pipe system with an internal diameter of 101.6 mm and a serpentine geometry. The experimental matrix consists of superficial gas and liquid velocities in ranges of 0.15–30 m/s and from 0.07 to 1.5 m/s, respectively, which cover bubbly to annular flow. The effects on the flow behaviours downstream of the 180° return bend are significantly reduced when the flow reaches an axial distance of 47 pipe diameters from the U-bend. Therefore, reasonably developed flow is attained at this development length downstream of the bend. Other published measurements for large-diameter film thickness show similar trends with respect to the superficial gas velocity. However, the trends differ from those of small-diameter pipes, with which the film thickness decreases much faster with increasing gas flow. As a result, only a few of the published correlations for small pipe data agreed with the experimental data for large pipe film thickness. We therefore modified one of the best-performing correlations, which produced a better fit. Qualitative and statistical analyses show that the new correlation provides improved predictions for two-phase flow film thickness in large-diameter pipes.
Keywords: Conductance film probes; Large diameter pipes; Multiphase flow; Return bends; Wire mesh sensor